ABOUT THE FOUNDERS OF LEGAL SOCIOLOGY AND THEIR IDEAS - MIRELA CRISTIANA NILĂ STRATONE (Challenges of the Knowledge Society)
The main founders of the juridical sociology are considered to be Eugen Ehrlich, Max Weber, Theodor Geiger and Georges Gurvitch, The researches of juridical sociology from Romania are demonstrating the existence of a real tradition in this domain at a national standard. Some roumanian explores of formation jurists have practicated in the cognitive demarche a sociologycal abordation about the law, what have been fatal conduced to the fixing of the base of the juridical sociology in Romania.